Elderly Assistant Based on Facial Emotion and Posture Analysis - Mandeep Kumar Sinha; Dr Ravindra M (IJRDO - Journal of Electrical And Electronics Engineering, 2020)
These paper presents the facial recognition to assists knee joining elderly people for independent living in their own homes. It reduces the health expenditures and burden of health care professionals in care family units. Facial expressions are one of the key features of human being and it can be used to speculate emotional state at a particular moment. This paper employs the Convolution Neural Network and Deep Neural Network to develop a facial recognition model that categorizes a facial expression into some different emotion categorizes Afraid, Angry, Disgusted, Happy, Neutral, Sad and Surprised. This project is mainly developed for Knee joining elderly person the person who are notable to take care of by themselves so we take care of them based on their facial emotion what actually they need sad also we have some senor called accelerometer to detect the fall detection of person based on the accelerometer movements.